Rarity as an indicator of endangerment in neotropical frogs - Toledo, Luis Felipe; Becker, C. Guilherme; Haddad, Celio Fernando Baptista [UNESP]; Zamudio, Kelly R. (Elsevier B.V., 2014)
Anurans are endangered worldwide and declining populations are in need of urgent conservation management. Optimal conservation actions ideally rely on basic ecological and natural history data, such as population size, habitat requirements and availability, or biotic interactions. Unfortunately, we lack basic natural history information for most frogs, making it difficult to determine species vulnerability in nature. Our goal in this study was to apply a 'rarity' index to assess whether rarity and other endangerment assessment criteria can serve complementary roles in conservation prioritization. We applied Rabinowitz' "eight forms of rarity" classification, which is based on geographic range, habitat specificity, and local population size, to evaluate its value as an indicator of species vulnerability in the anuran assemblage endemic to the Atlantic Coastal Forest of Brazil. We compared patterns of rarity in anurans to IUCN endangerment status, and investigated possible relationships between spatial traits (topographic complexity, elevation, and latitudinal variation) and groups of species with different forms of rarity. We found similar patterns of rarity across taxonomic groups and among local anuran communities, indicating that these patterns are consistent across taxa and geographic scales. We provide evidence that rarity rankings increase in areas of higher elevation and topographic complexity. Our results also indicate that the majority of rare species are classified as threatened according to IUCN; however, 32 species ranked as rare are still considered 'least concern' or 'data deficient' by the current Brazilian red list of threatened species. We propose that including rarity categories in endangerment assessment for anurans can improve our ability to prioritize conservation efforts for threatened amphibian taxa. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Abundance; Amphibian conservation; Brazil; Endangered species; IUCN